2016
DOI: 10.1038/ncomms11037
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation induced by C3aR-dependent NETosis drives protumorigenic neutrophils during small intestinal tumorigenesis

Abstract: Excessive activation of blood coagulation and neutrophil accumulation have been described in several human cancers. However, whether hypercoagulation and neutrophilia are linked and involved in cancer development is currently unknown. Here we show that spontaneous intestinal tumorigenesis correlates with the accumulation of low-density neutrophils with a pro-tumorigenic N2 phenotype and unprompted neutrophil extracellular traps (NET) formation. We find that increased circulating lipopolysaccharide induces upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
176
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(192 citation statements)
references
References 70 publications
(81 reference statements)
13
176
1
2
Order By: Relevance
“…A similar neutrophil phenotypic duplicity has been identified in the blood of tumor-bearing mice and cancer patients based on separation by density gradient 55, 75 . In these samples, elevated levels of both immature and mature neutrophil populations were found in the low-density fraction, collectively termed low-density neutrophils (LDNs), in addition to the previously named tumor-entrained neutrophils (TENs) in the high-density layer, termed high-density neutrophils (HDNs).…”
Section: Neutrophil Heterogeneity and Plasticitysupporting
confidence: 55%
“…A similar neutrophil phenotypic duplicity has been identified in the blood of tumor-bearing mice and cancer patients based on separation by density gradient 55, 75 . In these samples, elevated levels of both immature and mature neutrophil populations were found in the low-density fraction, collectively termed low-density neutrophils (LDNs), in addition to the previously named tumor-entrained neutrophils (TENs) in the high-density layer, termed high-density neutrophils (HDNs).…”
Section: Neutrophil Heterogeneity and Plasticitysupporting
confidence: 55%
“…Mechanistically, circulating lipopolysaccharide, likely leaking from the intestine, appears to induce complement activation and upregulate the expression levels of C3aR on neutrophils. C3aR-mediated signalling then triggers NET release, coagulation pathways and polarization of neutrophils towards a pro-tumorigenic phenotype 78 .…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 99%
“…However, whether either of these neutrophil populations had a preformed identity or whether they were moulded by the local tissue microenvironment was not resolved. Similarly, in the study by Guglietta et al 3 , a low-density (N2) neutro phil subtype could be found in the local tumour environment, but these cells could also be found in the peripheral blood, implying the existence of multiple phenotypes prior to recruitment. Although it has been previously suggested that neutrophils might play a part in clot formation 7 , the latest study provides evidence that these clots act to further shape neutrophil function.…”
Section: Craig N Jenne and Paul Kubesmentioning
confidence: 90%
“…This approach involves the administration of monoclonal antibodies to neutralize VEGF, resulting in reduced vascularization of the tumour. Interestingly, only small tumours seemed to benefit from systemic coagulation, whereas larger tumours appear more dependent on vascularization and blood flow, suggesting fundamental differences between tumour types 3,10 .…”
Section: Craig N Jenne and Paul Kubesmentioning
confidence: 94%
See 1 more Smart Citation